Numerical Solution On MHD Flow And Heat Transfer For The Upper-Convected Maxwell Fluid Over A Stretching/Shrinking Sheet - Ishak, Nazila; Waini, Iskandar; Mohamed, Muhammad Khairul Anuar; Rosli, Norhayati; Salleh, Mohd Zuki (Pustaka Aman Press Sdn. Bhd., 2017)
In this paper we will discuss the effect of magnetohydrodynamic (MHD) towards the flow and heat transfer for the Upper-Convected Maxwell (UCM) fluid over a stretching/shrinking sheet with prescribed wall temperature (PWT). A similarity transformation is used to reduce the governing equations to a set of ordinary differential equations (ODEs), which are then solved numerically using Shooting method. The effect of various parameter such as the Prandtl number, the magnetic parameter, the suction parameter, the stretching or shrinking parameter, and the Maxwell parameter are considered. The results obtained under the special cases are illustrated graphically and compared with previous results to support their validity.